الإطار القانوني للانتقال الطاقوي في الجزائر - علجية قناوي (My University, 2024)
summary: At present, the topic of energy transfer to energy alternatives capable of addressing the threat of depletion of traditional energy resources and as a solution to the growing demand for energy without posing threats to the environment is one of the emerging issues on the international scene, for which renewable energies have been the best solution. These sources are the only viable and safe way to overcome environmental problems and achieve sustainable development. Accordingly, the study aims to highlight Algeria ' s legal approach, through which the new energy approach can be adopted by abandoning the traditional, depleted and polluting energies of the environment and relying on renewable energies for environmental conservation and sustainable development. In this context, it has adopted a number of strategies and programmes based on the legal and regulatory texts and institutions that frame the process, despite the obstacles and challenges that continue to hamper its development in the hope of overcoming them and finding solutions in the future. ............................ المخلص: يعد موضوع الانتقال الطاقوي في الوقت الحالي ، نحو بدائل طاقوية قادرة على مواجهة خطر نضوب موارد الطاقة التقليدية و كحل لمواجهة الطلب المتزاید على الطاقة دون ان يشكل ذلك تهديدات على البيئة، احدى القضايا المستجدة على الساحة الدولية حاليا والتي اتخذت من الطاقات المتجددة الحل الامثل لها، لما تتميز به هذه المصادر من ديمومة ونقاوة فهي السبيل الوحيد والامن للتغلب على المشاكل البيئية وتحقيق التنمية المستدامة، وعليه تهدف الدراسة الى ابراز النهج القانوني الذي سلكته الجزائر والذي بواسطته يمكن تبني نموذج النهج الطاقوي الجديد وذلك بالتخلي عن الطاقات التقليدية الناضبة والملوثة للبيئة والاعتماد على الطاقات المتجددة للمحافظة على البيئة وتحقيق التنمية المستدامة ،حيث تبنت في هذا الاطار العديد من الاستراتيجيات والبرامج بالاعتماد على النصوص قانونية والتنظيمية والمؤسسات المؤطرة لهذه العملية بالرغم من العوائق والتحديات التي لاتزال تعيق تطورها على امل تجاوزها وايجاد الحلول لها في المستقبل. ............................. Résumé : Le sujet de la transition énergétique vers des alternatives capables de faire face à l'épuisement des ressources énergétiques traditionnelles et de répondre à la demande croissante en énergie sans menacer l'environnement est l'une des questions émergentes sur la scène internationale actuelle. Les énergies renouvelables sont considérées comme la solution optimale en raison de leur durabilité et de leur propreté. L'étude vise à mettre en évidence l'approche juridique adoptée par l'Algérie, qui permet d'adopter un nouveau modèle énergétique en abandonnant les énergies traditionnelles épuisées et polluantes au profit des énergies renouvelables pour préserver l'environnement et réaliser un développement durable. Malgré les obstacles et les défis, plusieurs stratégies et programmes ont été adoptés dans ce cadre, en s'appuyant sur des textes juridiques, des réglementations et des institutions encadrant ce processus, dans l'espoir de les surmonter et de trouver des solutions à l'avenir.